Therapeutic Impact Of Ayurveda On Hypothyroidism - Manish, Acharya; Chaudhary, Gitika; Richa; Walia, Bhawna; Rani, Tanu (International Research Journal of Ayurveda & Yoga, 2026)
Hypothyroidism, a common endocrine disorder marked by reduced thyroid hormone production, often presents with systemic effects and can lead to or exacerbate polycystic ovary syndrome (PCOS), particularly through metabolic and hormonal disturbances. This case study documents the Ayurvedic management of a 25-year-old female diagnosed with hypothyroidism-associated PCOS, who presented at Jeena Sikho Lifecare Limited Hospital, Gurugram, Haryana, India, on February 25, 2025. The patient initially reported symptoms of weight gain, neck swelling, increased appetite, and menstrual irregularity. Laboratory investigations revealed severely elevated TSH levels (>150.0 uIU/ml), abnormal T3 (90.6 ng/ml), and T4 (2.9 µg/dl) values. Ayurvedic treatment focused on correcting dosha imbalances, rekindling Agni, reducing Kapha and Meda, and restoring hormonal equilibrium using internal Ayurvedic medications and dietary/ lifestyle modifications. Over a treatment span of approximately two months, the patient showed significant biochemical improvements: TSH reduced to 10.410 uIU/ml, with corresponding normalization of T3 and T4 levels. Symptomatically, she reported relief from menstrual irregularities and other systemic complaints. This case highlights the potential of Ayurvedic protocols in effectively managing hypothyroidism and its sequelae like PCOS. However, more comprehensive clinical studies are warranted to standardize treatment approaches and validate efficacy.